Finely Tuned Porous Coordination Polymers To Boost Methane Separation Efficiency. Issue 37 (6th June 2019) - Wang, Yang; Dong, Qiubing; Cao, Haifei; Ji, Wei; Duan, Jingui; Jing, Su; Jin, Wanqin
Abstract: Absorbents with high breakthrough efficiency and weak host–guest interaction are considered to be promising candidates for an energy‐saving process in feasible pressure/volume swing adsorption (PSA/VSA). Herein, two groups of finely designed Fe‐ and Co‐based porous coordination polymers (PCPs) are proposed and validated; these possess hourglass‐shaped nanochannels, through the cooperation of T‐shaped ligands with shifted methyl groups. Featuring optimal nanochannels, high static adsorption, and relatively lower binding energy, one of these polymers, named NTU‐30, enables significant C2 H6 /CH4 and C2 H4 /CH4 breakthrough efficiency, with approximately 1.0 or 0.6 g CH4 (100 %) harvested from the corresponding mixtures using 1 g of sample at ambient temperature. Furthermore, the positive effect of aromatic sites within NTU‐30 is detected and investigated through an in situ IR study. Abstract : Methane purification : Featuring optimal nanochannels, a new coordination polymer, NTU‐30, shows a significant C2 H6 /CH4 and C2 H4 /CH4 breakthrough efficiency: 1.0 or 0.6 g CH4 can be harvested from the mixtures using 1 g sample bed at ambient temperature (see figure).